Karakteristik Batang dan Sifat Fisika Bambu Tali (Gigantochloa apus (Bi. Ex Schult.) Kurz) di Kawasan HKm Desa Aik Bual, Kabupaten Lombok Barat, Indonesia - Febriana Tri Wulandari; Ni Putu Ety Lismaya Dewi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Communities well know non-Timber Forest Product (NTFP) of bamboo with properties, strong culm, flexible, straight, smooth, hard, easily split and formed, very doable, and light transported easily. Besides those, bamboo is relatively inexpensive compared to other raw materials found in the village community’s vicinity. One of the bamboos found in Aik Bual Village’s community forests was tali bamboo (G. apus). Identification of G. apus was required to understand its characteristics, while the physical properties would be useful for understanding its dimension stabilities. The objectives of this study were to identify the stem characteristics and physical properties of G. apus. Experimental method was employed to conduct the study. Three culms were selected, and each culm was divided into three sections: bottom, middle, and top. Physical properties were tested using India Standard number IS 6874, 2008. The characteristics of G. apus were: the intermodal space of the bottom culm was 31.2-38.5 cm, the middle culm was 40-47 cm, and the top culm was 26-60.8 cm; the diameter of the bottom culm was 5.77-6.38 cm, the middle culm was 5.72-6.48 cm, and the top culm was 5.18-6.19 cm; the thickness of bottom culm was 0.9-1.35 cm, the middle was 0.55-0.96 cm, and the top was 0.54-0.76 cm. Physical properties of G. apus were: the fresh moisture content was 111.23%-143.24%, the air-dried moisture content was 11.78-12.72%, while the fresh density was 0.47-0.56, the air-dried density was 0.59-0.64, and the oven-dried density was 0.60-0.63.